A Study on Statistical Recurrence of Some Distinguishing Features of Handwritings and Signatures - Pradhan, M.; Bhusal, B.P.; Bhattarai, P.; Shakya, P.M.; K.C., Bashudev; Bajracharya, M. (Scientific World, 2020)
A hundred of different cases with questioned handwritings and signatures of a hundred different individuals written on the time interval from one year to sixty-one years were studied and the twenty five distinguishing characteristics were found to recur in different extents. A total of 764 points were noted with average of 7 to 8 points per case and statistics of recurrence of the same characteristics was built up so as to explain the most recurring and least recurring characteristics of the writings and signatures that resembled to assert the common origin even after the long interval of time. Amidst the variables, the 'design of letters and specific patterns' was found to be the most recurring whereas 'tie formation' and 'position, shape and size of dot (.)' were found to be the least.